Genetic and epigenetic factors underlying sex differences in the regulation of gene expression in the brain. Issue 1 (2nd January 2017) - Ratnu, Vikram S.; Emami, Michael R.; Bredy, Timothy W.
Abstract : There are inherent biological differences between males and females that contribute to sex differences in brain function and to many sex‐specific illnesses and disorders. Traditionally, it has been thought that such differences are due largely to hormonal regulation; however, there are also genetic and epigenetic effects caused by the inheritance and unequal dosage of genes located on the X and Y chromosomes. Here we discuss the evidence in favor of a genetic and epigenetic basis for sexually dimorphic behavior, as a consequence of underlying differences in the regulation of genes that drive brain function. A better understanding of sex‐specific molecular processes in the brain will provide further insight for the development of novel therapeutic approaches for the treatment of neuropsychiatric disorders characterized by sex differences. © 2016 Wiley Periodicals, Inc.